Progression-Free Survival and Time to Progression as Potential Surrogate Endpoints for Overall Survival in Chemoradiotherapy Trials in Limited-Stage Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis - Yang, Yin; Wang, Jianyang; Wang, Wenqing; Zhang, Tao; Zhao, Jingjing; Wang, Yu; Li, Yexiong; Wang, Luhua; Bi, Nan (Frontiers in Oncology, 2022)
Purpose: To investigate whether progression-free survival (PFS) or time to progression (TTP) could be valid surrogate endpoint for overall survival (OS) in patients with limited-stage small-cell lung cancer (LS-SCLC) receiving combined chemoradiotherapy. Methods: Literature searching was performed in PubMed, Embase, and The Cochrane Library up to 2021. Prediction models were firstly established using data from phase Ⅲ randomized controlled trials (RCTs), and then externally validated in phase Ⅱ and retrospective studies. Correlation analysis was evaluated by weighted linear regression model at both trial- and arm-level. Cross-validation was performed to assess the consistency and robustness of the established models. Results: 37 researches, including 15 phase Ⅲ RCTs, 12 phase Ⅱ and 10 retrospective studies, were selected in final analysis. In trial-level surrogacy, very good correlation was observed between hazard ratios (HRs) of PFS/TTP and OS (R2=0.783, 95%CI 0.771–0.794). In arm-level surrogacy, very good correlations were also observed between 2-year (R2=0.823, 95%CI 0.814–0.832), 3-year (R2=0.843, 95%CI 0.833–0.850), 5-year (R2=0.852, 95%CI 0.843–0.859) PFS/TTP and 5-year OS. An excellent correlation was observed between 4-year PFS/TTP and 5-year OS (R2=0.906, 95%CI 0.901–0.910). Cross-validation demonstrated reasonable overall consistency. External validation in phase Ⅱ and retrospective studies showed good agreement (R2, 0.728–0.824). Conclusions: PFS/TTP was valid surrogate endpoint for OS in patients with LS-SCLC receiving combined chemoradiotherapy. The finding provides high-level evidence to support PFS/TTP as the primary endpoint in clinical trials so as to speed up introducing novel agents to the treatment of LS-SCLC.